1993
DOI: 10.1055/s-2007-994029
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis in Children Undergoing Liver Transplantation

Abstract: We reviewed the records of 200 children who underwent 238 orthotopic liver transplantations in order to determine which preoperative factors could predict intraoperative blood loss. A coagulation abnormality score (CAS) was calculated by allowing one point for each abnormality in six preoperative coagulation tests. The mean CAS values were significantly greater in children suffering from fulminant hepatic failure (Fulm) or post-necrotic cirrhosis (PNC) and those having retransplantation (ReTx) than in those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…1,5,[27][28][29][30] For pediatric liver transplants, apart from retransplantation, factors that have been associated with increased intraoperative blood losses include: hypoplastic portal vein, use of a reduced-size liver graft, requirement of in-hospital supportive care, intra-abdominal malformations and signs of severe liver failure (encephalopathy, ascites, prolonged PT). 20,[31][32][33] Children younger than two years, and particularly those under one year of age experience higher blood loss. 34,35 Transplantation of a reduced (fraction of an adult human organ) liver not only increases intra-and postoperative blood loss, but has been associated with an increase in the percentage of patients undergoing reoperation for continued blood loss, from 9.6 to 19.2%.…”
mentioning
confidence: 99%
“…1,5,[27][28][29][30] For pediatric liver transplants, apart from retransplantation, factors that have been associated with increased intraoperative blood losses include: hypoplastic portal vein, use of a reduced-size liver graft, requirement of in-hospital supportive care, intra-abdominal malformations and signs of severe liver failure (encephalopathy, ascites, prolonged PT). 20,[31][32][33] Children younger than two years, and particularly those under one year of age experience higher blood loss. 34,35 Transplantation of a reduced (fraction of an adult human organ) liver not only increases intra-and postoperative blood loss, but has been associated with an increase in the percentage of patients undergoing reoperation for continued blood loss, from 9.6 to 19.2%.…”
mentioning
confidence: 99%
“…43,44 TMA is also reported to be one of the most important complications in liver transplantation. 5,45 Perioperative defects in the hemostasis system can be extensive and depend on the underlying disease. They usually resemble those illustrated in Table 4.…”
Section: Liver Cirrhosismentioning
confidence: 99%
“…The reticuloendothelial system (RES) of the liver greatly participates in the clearance of breakdown products of activated clotting factors such as fibrin-related products, thrombin-antithrombin complex (TAT), plasmin-plasmin-inhibitor complex (PPIC), and activated platelets. Prof. Mammen was an early pioneer in the investigation of various hemostatic abnormalities associated with many liver diseases including liver cirrhosis, and several liver abnormalities due to liver transplantation 5 or bone marrow transplantation 6 have been recently noted.…”
mentioning
confidence: 99%
“…Table 2 summarizes some of these studies each of which comes from a different Institution involving a minimum of 50 patients with at least two haemostasis assays. However, most authors failed to ®nd any correlation between preoperative haemostatic pro®le and blood requirements in adults [23,24] or children [22,25]. Two studies found a relationship between abnormalities in some preoperative coagulation tests and blood requirements.…”
Section: Preoperative Screeningmentioning
confidence: 99%